Research activity on the web: role of students and searching needs in a Malaysian local university - Ismail, M.A.; Yaacob, M.; Kareem, S.A. (2008)
Research is a systematic activity in searching for new information and understanding. World Wide Web (WWW) supplies trillions of information to feed the research purposes. Scholarly publications in particular, provide specific information to contribute in generating a new body of knowledge. This paper will specifically look at the role of novice research students (from both undergraduate and postgraduates level) and the need-and-want while searching for scholarly contents. The survey took place in the Faculty of Computer Science and Information Technology, University of Malaya, Malaysia with 77 undergraduates (Final Year Students) and 53 postgraduatesâ students. The questionnaire consists of five sections for undergraduates and six sections for postgraduate. The main different between the questionnaire is that for the postgraduate part, we add another section particularly to elicit students publishing history. The result shows that majority of the student spent six to ten hours a week to search for information for research purposes. Online search engines are the major sources for information. Complete electronic theses and final year studentsâ project are rated highest to be the type of work that postgraduates and undergraduates wish to deposit in institutional repository. Efficient keywords search and free to use are chosen by the majority of the student as the factors that will motivate them to use the repository. This paper will outline overall result of the survey and highlights the analysis of the searching behavior section. We will conclude the paper with the direction of future works.